Städtebaulicher Ideenwettbewerb Westliche Unterstadt Mannheim. - (:unkn) unknown (My University, 1977)
1. Preis A. Lange, H. Mitzlaff, J. Böhm, C. Müller (Mannheim) 2. Preis Prof. P. Serini, G. Reinwald, G. Rumpf (Mannheim/Neustadt) 3. Preis A. Plattner, W. Heinecke (Mannheim) 4 Ankäufe.
Keywords: Städtebaulicher Wettbewerb; Stadtplanung; Planung